A case study in the use of ocean circulation and particle-tracking models to quantify connectivity among Marine Protected Areas in Canadian Atlantic waters - Ohashi, Kyoko; Sheng, Jinyu; Hatcher, Bruce G. (Frontiers in Marine Science, 2025)
One measure of the effectiveness of Marine Protected Areas (MPAs) is their relationship to each other as source or sink areas of marine organisms at different life stages. Here we use the ocean circulation model ROMS (Regional Ocean Modeling System), coupled to the sea ice model CICE (Community Ice CodE), and the particle-tracking model ROMSPath to estimate connectivity among MPAs located off the Atlantic coast of Canada. The focus of this study is on connectivity in terms of passive particles (i.e., particles whose movements are sums of advection by simulated currents and small, random movements that represent the effect of sub-grid scale circulation features). ROMS and CICE are used to simulate the daily-mean, three-dimensional (3D) ocean state during 2015–2018, which are averaged into seasonal means and used as inputs for ROMSPath. Three MPAs are considered: Banc-des-Américains (BdA) in the Gulf of St. Lawrence, Saint Anns Bank (SAB) in Cabot Strait between the Gulf of St. Lawrence and the Scotian Shelf, and Gully on the offshore edge of the Scotian Shelf. In each experiment, passive particles are released in an MPA, at the 5-m depth, into a seasonal-mean, 3D circulation field and tracked for 90 days. Particle distributions after 30, 60, and 90 days, composited for each season over 2015–2018, are used to assess the results of the experiments. The results indicate the strongest connection among the MPAs occurs between the SAB and Gully MPAs in the summer, with 11% of particles released from the former being in the latter after 60 days, followed by BdA and SAB in the winter with 8% of particles from the former being in the latter after 90 days. Connection between the BdA and Gully MPAs is weak, and year-to-year variability among the experimental results suggests this weak connection is influenced by variability in the St. Lawrence River’s discharge. The experimental results suggest the BdA and SAB MPAs can act as source areas to downstream MPAs for larvae of snow crab, a commercially important species in the region. We also qualitatively examine the role of ROMSPath’s horizontal diffusivity (which controls the particles’ small, random movements).